Search 83,181 tutors
FIND TUTORS
Ask a question
0 0

-2(8n-4)=8(1-n)

Tutors, please sign in to answer this question.

2 Answers

-2(8n - 4) = 8(1 - n) 

Let's use distributive property to open parentheses 

-2 • 8n - (-2) • 4 = 8 • 1 - 8 • n 

- 16n + 8  =  8 - 8n 
         - 8    - 8 

- 16n = - 8n 
+ 8n    + 8n 

- 8n = 0 -----> n = 0 

Comments

-2(8n-4) = 8(1-n)
 
 
1) Multiply - remember to use plenty of brackets
 
(-2*8n) + (-2*4) = (8*1) + (8*-n) --->
 
-16n + 8 = 8 + -8n
 
 
2) Bring all terms with n to one side -->
 
-8n + 8 = 8
 
3) Divide all terms by 8  -->
 
-n + 1 = 1
 
4) Solve -->
 
n = 0